Does Consumption of Omega-3 Polyunsaturated Fatty Acids Affect Lipid Profile and Fasting Blood Glucose in Patients With Traumatic Spinal Cord Injury? A Double-Blinded Randomized Clinical Trial. Issue 4 (October 2015) - Sabour, Hadis; Javidan, Abbas Norouzi; Latifi, Sahar; Shakeri, Hania; Arman, Farid; Larijani, Bagher; Shidfar, Farzad; Heshmat, Ramin; Razavi, Seyed-Hassan Emami; Vafa, Mohammad Reza
Abstract : Omega-3 polyunsaturated fatty acids (ω-3 PUFAs) have been shown to influence serum lipids. However, these effects have not yet been evaluated among patients with spinal cord injury. In this double-blinded randomized clinical trial, 104 subjects with spinal cord injury were randomly assigned to intervention and control group and were followed for 14 months. The treatment group received 2 MorDHA capsules (435 mg of docosahexaenoic acid and 65 mg of eicosapentaenoic acid, daily), and the control group received placebo capsules daily. There were no significant changes in lipid profiles, blood glucose, and weight. However, the linear relationship between weight and low-density lipoprotein that was observed at the beginning of the trial ( P = .04, r = 0.28) was attenuated after 14 months of intervention. It seems that the lipid profile modulation as a response to ω-3 PUFA therapy is not significant in patients with spinal cord injury.